Do University Based Regions Really Attract Outside Entrepreneurs: The Case of the German Biotechnology Industry - Dirk Engel; Oliver Heneric (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
The paper tests empirically the role of knowledge stocks to explain the regional distribution of Germany?s biotechnology founders. We present an unique approach to highlight the role of knowledge spillovers as we differentiate according the local embeddedness and research affinity of founders. As expected, the results of our multivariate analysis indicate a high start-up activity in knowledge intensive regions. Group differentiation shows that knowledge stock variables matter only for academic founders inside as well as outside the region. In contrast, the start-up activity of non-academic founders coming from inside or outside the region cannot be explained with knowledge intensity of the region. Our empirical results suggest that knowledge spillovers matter, but these spillovers only attract founders with high affinity to research.
Keywords: R58; C21; R30; O30; 330; Biotechnology; start-ups; economic geography; intellectual capital; count data model; Forschungskooperation; Biotechnische Forschung; Unternehmensgründung; Biotechnische Industrie; Standort; Wissen; Region; Schätzung; Deutschland